2018
DOI: 10.15218/zjms.2018.036
|View full text |Cite
|
Sign up to set email alerts
|

Cranial computed tomography scan findings in acute head injury

Abstract: Results: The age of the studied patients ranged from 2 to 67 years with a mean± SD of 29.23±15.1 with males dominating the sample (78.6%).Road traffic accident was the main cause of injury (65.7%).The most common indication for requesting a CT scan was an altered level of consciousness and vomiting. Intracranial CT scan findings related to head injury were seen in 82% of victims of which fractures (50%) and intracranial hematomas (45.2%) were the main findings followed by combined injuries(31.8) and soft tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In this study, both normal and abnormal CT outcomes were noted with male preponderance. This finding is in consonance with existing literatures also observing the same outcomes (Adogu et al, 2015;Akanji et al, 2015;Jamal, 2018;Onwuchekwa and Alazigha, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, both normal and abnormal CT outcomes were noted with male preponderance. This finding is in consonance with existing literatures also observing the same outcomes (Adogu et al, 2015;Akanji et al, 2015;Jamal, 2018;Onwuchekwa and Alazigha, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Linear (16.67%) and depressed (12.50%) were the specified fracture types frequently documented although the highest percentage was reported unspecified (50%). An Iraqi (Jamal, 2018) and Nigerian (Yusuf et al, 2014) studies recorded similar findings, but Tandle and Keoliya (2011) contrary observed depressed fracture as the least common fracture in their research. Apart from the above injuries, patient in our study sustained other injuries in highest frequencies, i.e.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations